Pengaruh Explosive Power Otot Tungkai Dengan Hasil Lompat Jauh Gaya Jongkok Siswa Kelas X Ips Sma Muhammadiyah Kabupaten Kampar - Fikri, Muhammad (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2022)
The purpose of the study. This study aims to determine whether there is an effect between explosive leg muscle power and the results of the students' long jump (Tuck) style. Materials and methods. This is due to the low physical condition of students so that they do not produce maximum explosive power of the leg muscles. This research was conducted using a correlational research design. Based on the results of research that has been carried out on students of Senior High School in Kampar Districs. Results. the value of count=0.811>ttable= 0.514. Obtained r = 0.811 including very strong category. Significance test using the t-test Significance formula. From the calculation results, it is known that t count = 5.006 while t table = 1.771. So t count = 5.006>ttable = 1.771. Thus, a conclusion can be drawn that: There is an effect of explosive power in the leg muscles with the results of the long jump squatting style for students of Senior High School in Kampar Districs. Conclusions. Thus, a conclusion can be drawn that: There is an effect of explosive power in the leg muscles with the results of the long jump (Tuck) style for students.